First Cold Spraying of Carbonated Biomimetic Nanocrystalline Apatite on Ti6Al4V: Physical–Chemical, Microstructural, and Preliminary Mechanical Characterizations1 . Issue 4 (28th December 2015) - Kergourlay, Emmanuelle; Grossin, David; Cinca, Nuria; Josse, Claudie; Dosta, Sergi; Bertrand, Ghislaine; Garcia, Irene; Guilemany, Jose Maria; Rey, Christian
Abstract : Carbonated Biomimetic Nanocrystalline Apatite (BNAc) coatings are obtained for the first time by Cold Spray. The coatings are characterized by FTIR, Raman, XRD, and SEM and compared to the powders. No significant chemical and structural changes are detected and the nanostructure features of these very reactive BNAc are preserved in the coating. These results and preliminary mechanical assays show that Cold Spray can produce an operational biomimetic coatings offering a high potential for implants functionalization and osseointegration. However, these first results need further studies in order to understand the mechanism of adhesion and the interactions at the coating–substrate interface. Abstract : Carbonated Biomimetic Nanocrystalline Apatite coatings, deposited by a Cold Spray system, used for the first time are characterized to determine the successfully manufacturing of this bioceramic coatings. Chemicals characteristics and nanometric size are largely saved. These results show that process can produce a biomimetic coating and has potential for improving integration of implants.